Evaluation of a new side-stream, low dead space, end-tidal carbon dioxide monitoring system in rats. (January 2014) - Beck, Christopher; Barthel, Franziska; Hahn, Anna-Maria; Vollmer, Christian; Bauer, Inge; Picker, Olaf
The aim of this study was to evaluate a newly developed infrared side-stream capnograph with minimal sample volume for the continuous measurement of end-tidal carbon dioxide (CO2 ) concentrations in small rodents. Thirty-four male Wistar rats (weight 345 ± 70 g) were treated in accordance with the National Institutes of Health (NIH) guidelines for animal care. All experiments were performed with approval of the local animal care and use committee. Sepsis was induced by implanting an 18 gauge stent into the colon 24 h prior to the experiments, allowing a constant fecal leakage into the peritoneal cavity (25 septic and nine control animals). Hemodynamic variables and end-tidal CO2 were recorded continuously and arterial blood (5 × 120 µL) was sampled periodically for arterial blood gas analysis. After baseline controlled mechanical ventilation was randomized and titrated to either normocapnia (35–45 mmHg) or hypercapnia (65–75 mmHg) with exogenous application of CO2 . A total of 155 paired CO2 measurements comparing end-tidal and arterial partial pressure were conducted. Side-stream capnography underestimated the CO2 partial pressure with a bias of −6.1 mmHg and a 95% limit of agreement from 6.7 to –19.1 mmHg. Our results suggest that side-stream end-tidal CO2 monitoring with a low dead space could be utilized in rats as a surrogate for the arterial CO2 measurement over a wide range of partial pressures in normal and septic animals.